KARAKTERISTIK MINERAL LEMPUNG HASIL UBAHAN PADA SUMUR LW-1 DAN LW-2 DENGAN MENGGUNAKAN METODE DIFRAKSI SINAR-X PADA SISTEM PANAS BUMI GUNUNG LAWU: THE CHARACTERISTICS OF CLAY MINERAL ALTERATION FROM WELLS LW-1 AND LW-2 USING X-RAY DIFFRACTION METHOD IN THE MOUNT LAWU GEOTHERMAL SYSTEM - Permana, S.T., M.T, Lano Adhitya; Sastrawijaya, Candra Widya; Hermawan, Dudi (Buletin Sumber Daya Geologi, 2020)
The LW-1 and LW-2 geothermal wells are located in the depression zone between Mount Lawu and Mount Jabolorangan contain rocks that are hydrothermally alterated as indicated by the presence of alteration minerals that are classified as argillic to advanced argillic alteration. To determine the character of the altered minerals that were formed, especially the presence of clay minerals in LW-1 and LW-2 wells, a study of clay minerals is required using the X-Ray Diffraction approach. This study aims to determine the presence and characteristics of clay minerals in LW-1 and LW-2 also their correlation to the formation of a geothermal system in the Gunung Lawu area. The analysis and interpretation using XRD method in LW-1 and LW-2 wells shows that within the temperature increases the crystal shape of the clay minerals becomes more perfect which is represented by a smaller degree of crystallinity. Whereas the effect of grain size on the XRD pattern shows that the crystallinity of the clay minerals tend to decrease with increasing grain size. The altered clay minerals in LW-1 and LW-2 wells consist of smectite, illite, kaolinite and halloysite which can be acted as caprock in the Mount Lawu geothermal system.